Improving Blood Plasma Glycoproteome Coverage by Coupling Ultracentrifugation Fractionation to Electrostatic Repulsion–Hydrophilic Interaction Chromatography Enrichment - Adav, Sunil S. (2016)
Blood plasma is considered to be an excellent source of disease biomarkers because it contains proteins, lipids, metabolites, cell, and cell-derived extracellular vesicles from different cellular origins including diseased tissues. Most secretory and membranous proteins that can be found in plasma are glycoproteins; therefore, the plasma glycoproteome is one of the major subproteomes that is highly enriched with disease biomarkers. As a result, the glycoproteome has attracted much attention in clinical proteomic research. The modification of proteins with glycans regulates a wide range of functions in biology, but profiling plasma glycoproteins on a global scale has been hampered by the presence of low stoichiometry of glycoproteins in a complex high abundance plasma proteome background and lack of effective analytical technique. This study aims to improve plasma glycoproteome coverage using pig plasma as a model sample with a two-step strategy. The first step involves fractionation of the plasma proteins using ultracentrifugation into supernatant and pellet that is believed to contain low abundant glycoproteins. In the second step, further enrichment of glycopeptides was achieved in both fractions by adopting electrostatic repulsion hydrophilic interaction chromatography (ERLIC) coupled to tandem mass spectrometry (LC-MS/MS) analysis. The coverage of enriched glycoproteins in supernatant, pellet, and whole plasma sample as control was compared. Using this simple sample fractionation approach by ultracentrifugation and further ERLIC enrichment technique, sample complexity was reduced and glycoproteome coverage was significantly enhanced in supernatant and pellet fractions (by >50%) compared with whole plasma sample. This study showed that when ultracentrifugation is coupled to ERLIC glycopeptides enrichment and glycoproteome identification are significantly improved. This study demonstrates the combination of ultracentrifugation and ERLIC as a useful method for discovering plasma glycoprotein disease biomarkers.